Escola multisseriada: desafios para formação de licenciados em pedagogia - Torres, Mayara Araújo (Universidade Federal do Tocantins, 2019)
The article entitled, Multisseries School: Challenges for the Education of Graduates of Pedagogy, initially brings the socio-historical cultural context of the municipality of Arraias-TO, presenting the historicity of its 278 years, reaffirming its identity and recording a story little told in its reality. Later, the work presents us the educational presuppositions of the municipality, listing the organization of the pedagogical work in the context of rural schools and with its multi-seriado teaching. In order to better describe this type of organization within the scope of the multiseries, the article reports the experience of the compulsory stage of the Pedagogy degree course at the Federal University of Tocantins, noting how there is a dichotomy between what is set as a Pedagogical Course Project - Pedagogy PPC and the existing pedagogical practice in the initial training of the course.